Save the farm [videorecording (DVD)] - Silverstone, Alicia; Smart, Amy, 1976-; Hannah, Daryl (EarthNow!, 2013)
Save the farm tells the story of the largest urban farm in the United States, 14-acres sitting right in the middle of South Central Los Angeles. For 14 years over 350 families had cultivated this farm, feeding themselves and thousands in their community local organic food. When the city sells it to a developer in a closed-door meeting, activists and celebrities stage an 11th hour tree sit to save the farm. As the 5-year anniversary of the eviction approaches, director Michael Kuehnert demonstrates how a local community can come together to fight to save a farm they have come to depend on for their survival.